Graves' ophthalmopathy: the role of diffusion-weighted imaging in detecting involvement of extraocular muscles in early period of disease - Kilicarslan, R; Alkan, A; Ilhan, M M; Yetis, H; Aralasmak, A; Tasan, E (British journal of radiology, 2015)
To evaluate involvement of the extraocular muscle (EOM) using diffusion-weighted imaging (DWI), to determine whether there is correlation with conventional orbital MRI and apparent diffusion coefficient (ADC) values in patients with Graves' ophthalmopathy (GO). 35 patients known clinically with GO and 21 healthy controls were studied. Patients were assessed with clinical activity scores. All subjects underwent conventional MRI and DWI study. Involvement of the EOM was evaluated. The patients were classified as involved or uninvolved on orbital MRI and their ADC values in DWI compared. There was significant difference in the mean ADC value of all the EOMs in patients vs controls. The ADC values of all the EOMs were higher in patients. There were significant differences in ADC values between uninvolved muscles on conventional MRI and controls for the MR, SR and LR. There was no significant difference in ADC value between the two groups when considering the IR. ADC values of medial, lateral and superior rectus muscles were increased. Increased ADC values of the EOM in patients with GO suggest that EOM damage begins at a very early stage before being detected on routine orbital MRI. The routine MRI with DWI sequence will be a useful adjunct in the selection of a group of patients most likely to benefit from early treatment. This study can help to evaluate the involvement of GO in early period with MRI added DWI.